THE RELATIONSHIP BETWEEN KNEE HEIGHT, ULNA LENGTH, AND ARM SPAN WITH BODY HEIGHT AS AN APPLICATION OF NUTRITIONAL STATUS ASSESSMENT IN CEREBRAL PALSY CHILDREN - Nur Lathifah Mardiyati; Norma Diena Amalia; Niken Asih Pangastuti (Pontianak Nutrition Journal (PNJ), 2024)
In children with Cerebral Palsy (CP), measuring height (H) will be difficult to do in an optimal position. When measuring height in a standing position cannot be done, segmental measurements can be used, one of which is measuring knee height (KH), arm span (AS) and ulna length (UL). Based on this study, the proposer wants to research the relationship between knee height, ulna length and arm span with actual body height in healthy children so that it can then be applied to children with CP in Indonesia. This research uses an observational method with a cross-sectional design. The research subjects were 32 healthy children aged 6-12 years. The inclusion criteria are that the child has good nutritional status and is not sick. This research will use primary data which includes data on date of birth, age, gender, height, body length, knee height, ulna length and arm span. The tools used include respondents' personal data questionnaires, stadiometers, tape measure and calipers. Statistical analysis used the Shapiro-Wilk normality test. For the difference test with one-way ANOVA, it is said to be significant if p<0.05. After testing the differences between each H estimation formula from KH, AS and UL measurements and the actual H measurement results, it was discovered that these three H estimation formulas were significantly different from the actual H measurement results (p<0.000). Further research is needed to find an estimation formula that is more suitable for a larger number of subjects and considers other factors such as race, age, gender and body weight. Preparing measurement guidelines and designing special tools to measure height and/or other anthropometry in children with CP also needs to be carried out.